Comparison of the Uptake of Hepatocellular Carcinoma on Pre-Therapeutic MDCT, CACT, and SPECT/CT, and the Correlation with Post-Therapeutic PET/CT in Patients Undergoing Selective Internal Radiation Therapy - Meine, Timo C.; Brunkhorst, Thomas; Werncke, Thomas; Schütze, Christian; Vogel, Arndt; Kirstein, Martha M.; Dewald, Cornelia L. A.; Becker, Lena S.; Maschke, Sabine K.; Kretschmann, Nils; Wacker, Frank K.; Hinrichs, Jan B.; et al. (Journal of clinical medicine, 2021)
(1) Background: To comparatively analyze the uptake of hepatocellular carcinoma (HCC) on pre-therapeutic imaging modalities, the arterial phase multi-detector computed tomography (MDCT), the parenchymal phase C-arm computed tomography (CACT), the Technetium99m-macroaggregates of human serum albumin single-photon emission computed tomography/computed tomography (SPECT/CT), and the correlation to the post-therapeutic Yttrium90 positron emission tomography/computed tomography (PET/CT) in patients with selective internal radiation therapy (SIRT). (2) Methods: Between September 2013 and December 2016, 104 SIRT procedures were performed at our institution in 74 patients with HCC not suitable for curative surgery or ablation. Twenty-two patients underwent an identical sequence of pre-therapeutic MDCT, CACT, SPECT/CT, and post-therapeutic PET/CT with a standardized diagnostic and therapeutic protocol. In these 22 patients, 25 SIRT procedures were evaluated. The uptake of the HCC was assessed using tumor-background ratio (TBR). Therefore, regions of interest were placed on the tumor and the adjacent liver tissue on MDCT (TBRMDCT), CACT (TBRCACT), SPECT/CT (TBRSPECT/CT), and PET/CT (TBRPET/CT). Comparisons were made with the Friedman test and the Nemenyi post-hoc test. Correlations were analyzed using Spearman’s Rho and the Benjamini–Hochberg method. The level of significance was p < 0.05. (3) Results: TBR on MDCT (1.4 ± 0.3) was significantly smaller than on CACT (1.9 ± 0.6) and both were significantly smaller compared to SPECT/CT (4.6 ± 2.0) (pFriedman-Test < 0.001; pTBRMDCT/TBRCACT = 0.012, pTBRMDCT/TBRSPECT/CT < 0.001, pTBRCACT/TBRSPECT/CT < 0.001). There was no significant correlation of TBR on MDCT with PET/CT (rTBRMDCT/TBRPET/CT = 0.116; p = 0.534). In contrast, TBR on CACT correlated to TBR on SPECT/CT (rTBRCACT/TBRSPECT/CT = 0.489; p = 0.004) and tended to correlate to TBR on PET/CT (rTBRCACT/TBRPET/CT =0.365; p = 0.043). TBR on SPECT/CT correlated to TBR on PET/CT (rTBRSPECT/CT/TBRPET/CT = 0.706; p < 0.001) (4) Conclusion: The uptake assessment on CACT was in agreement with SPECT/CT and might be consistent with PET/CT. In contrast, MDCT was not comparable to CACT and SPECT/CT, and had no correlation with PET/CT due to the different application techniques. This emphasizes the value of the CACT, which has the potential to improve the dosimetric assessment of the tumor and liver uptake for SIRT.